2015
DOI: 10.2306/scienceasia1513-1874.2015.41.119
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity and DNA protective properties of rice grass juices

Abstract: Juice squeezed from cereal grasses harvested at the jointing stage, i.e., wheatgrass (Triticum aestivum), exhibits high antioxidant activity. Rice (Oryza sativa) may also exhibit antioxidant activity. We therefore examined the antioxidant activity of juices squeezed from grasses harvested at the jointing stage for seven coloured and seven white Thai rice cultivars. The antioxidant activity was determined using 2,2-diphenyl-1-picrylhydrazyl, ferric reducing antioxidant power, β-carotene bleaching, and thiobarbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 33 publications
0
28
0
1
Order By: Relevance
“…Choe et al [28] demonstrated that the DPPH scavenging capacity of ethanol extracts of barley leaves was 80.3 ± 0.41% at 5 mg/mL and that of methanol extracts was 79.5 ± 0.54% at 5 mg/mL. Khanthapok et al [29] in their study indicated that the DPPH scavenging capacity of wheat grass was 0.81 ± 0.02 IC 50 mg/mL. Rattanapon et al [30] estimated that the DPPH scavenging capacity of rice grass was 89.32 ± 0.57 mmol TE/g.…”
Section: Discussionmentioning
confidence: 99%
“…Choe et al [28] demonstrated that the DPPH scavenging capacity of ethanol extracts of barley leaves was 80.3 ± 0.41% at 5 mg/mL and that of methanol extracts was 79.5 ± 0.54% at 5 mg/mL. Khanthapok et al [29] in their study indicated that the DPPH scavenging capacity of wheat grass was 0.81 ± 0.02 IC 50 mg/mL. Rattanapon et al [30] estimated that the DPPH scavenging capacity of rice grass was 89.32 ± 0.57 mmol TE/g.…”
Section: Discussionmentioning
confidence: 99%
“…Even if rice grass juice gave less statistically ability on antioxidant activities, they still had comparable levels of antioxidant activities". A separate study (Khanthapoka et al 2015) has also demonstrated the antioxidant and DNA protection capacity of juice extracted from rice seedlings. Due to the differences in sample preparations, the results cannot be directly compared to the present study.…”
Section: Biochemical Assessments Of Rsementioning
confidence: 99%
“…However, further investigations are needed for testing this hypothesis, as the protective effects might not be a direct, or only, result of the antioxidant capacity. Units expressed as *per 100 g of fresh rice seedlings in this work and wheatgrass (Kulkarni et al 2006) and **per 100 g of dried extracts of rice seedling (Khanthapoka et al 2015). 1 mean ± standard deviation of three biological replicates.…”
Section: Biochemical Assessments Of Rsementioning
confidence: 99%
“…This has led to the development of a range of health foods and pharmaceutical products for health‐conscious consumers . More recently, the vegetative parts of purple rice plants have attracted attention as a source of antioxidants . Indeed, rice‐grass juice may contain more phenolic acids than the popular drink produced by macerating fresh wheat seedlings .…”
Section: Introductionmentioning
confidence: 99%
“…5 More recently, the vegetative parts of purple rice plants have attracted attention as a source of antioxidants. 6,7 Indeed, rice-grass juice may contain more phenolic acids than the popular drink produced by macerating fresh wheat seedlings. 8 Therefore, factors affecting the quality of antioxidants in staple and other foods should be taken into consideration when recommending agronomic practices to producers.…”
Section: Introductionmentioning
confidence: 99%